Banking fragility and financial crisis: evidence from SoutheastAsia / Norashikin Ismail... [et al.] - Ismail, Norashikin; Md Isa, Mohamad Azwan; Mazlan, Nurul Farhana; Abd Rahman, Nor Hadaliza (UiTM Cawangan Johor, 2019)
Throughout the 17 years of study period, the Southeast Asian countries were faced with three forms of financial crises namely Asian financial crisis, subprime crisis and currency crisis. Previous literatures have evidenced that banking fragility has been closely associated with financial crisis. Hence, this paper aims to construct the banking sector fragility index (BSFI) during the different forms of crises. Three Southeast Asian countries were selected based on their common economic fundamentals and top three largest gross domestic product (GDP) per capita i.e. Indonesia, Thailand and Malaysia which were studied from the year 2000 to 2016. The results indicate the Indonesian and Thailand banking sectors were seriously fragile after the Asian financial crisis (1997-1999). However, the fragility of banking sectors for these countries including Malaysia had diminished during the subprime crisis (2008-2009). Worst scenario repeated for the Indonesian banking sector when the currency crisis emerged in early 2014. Similarly, Malaysian banking sector confronted the worst level of fragility for the country following the depreciation of Malaysian ringgit against the US dollar at the end of 2014 to early 2015. This study shows that the three countries' banking sectors have responded differently to the three forms of financial crises.